Editorial - Guillen, Jorge (2018)
We are proud to release the 44th issue of the Journal of Economics, Finance and Administrative Science, edited by Emerald Publishing and indexed to the most prestigious databases, like Scopus. We are now ranked in the third percentile in Scimago. This is the result of the rigorous work that takes into account the demanding academic standards. The first article is “Determinants and forecast of the stock market activity of the Colombian Stock Market”. Using monthly data from 2007 to 2016, the authors found that stock market activity can be predicted in a large part by its lags, positive returns in the past three months, primary issues and the VIX index. The next article, titled “Competitive strategies and sport management”, uses resource-based theory to develop a model that integrates organizational actions with the variables that can moderate their impact on the performance of football clubs. This study provides several key contributions to the literature on organizational performance in the sports sector, with specific application for football clubs. Doi: https://doi.org/10.1108/JEFAS-06-2018-108